Renewable energy in community: economic impacts of the grid - Saarloos, Benjamin Alexander, author; Quinn, Jason, advisor; Bradley, Thomas, committee member; Burkhardt, Jesse, committee member; Olsen, Daniel, committee member (Colorado State University. Libraries, 2022)
The U.S. energy grid is a complex system that supports everyday lives. Grid energy has traditionally flowed in one direction from large, centralized power plants through transmission and distribution networks to corporate and residential consumers. However, with a growth in renewable energy systems (RES), energy flow has begun to take on a more bi-directional character with distributed generation, including excess energy generated by consumers being fed back to the energy grid. The breadth of individual energy use impacts and societal benefits attributed to growth in RES calls for analysis and development of RES on the community scale. Beyond the physical energy connection it provides, the grid can serve as an economic mechanism whereby RES can be sustainably developed through the grid, rather than an alternative to the grid. Measures have been developed to advance RES toward sustainability targets, recognizing that the grid plays an important enabling role. Net-zero energy is a classification system designed to reduce energy consumption in buildings and communities in support of climatic goals to reduce greenhouse emissions. A hierarchy of renewable energy supply options is established with a preference for on-site renewable energy over off-site supply options. Value of Solar (VOS) is an electric rate design mechanism intended to determine the true value of solar photovoltaic (PV) generated electricity. Beyond the obvious benefit of fossil fuel saved, VOS includes cost savings associated with avoided capacity, transmission & distribution cost deferral, and environmental benefits. Net-zero energy and VOS methodology are both identified as sustainability measures within a broader RES design process. Sustainable RES design recognizes that harmonizing economic, environmental, and social interests is a community effort. Case-studies present an opportunity to further develop a consistent set of design principles while simultaneously presenting unique and important results. In this work, a net-zero energy analysis is conducted for the National Wester Center in Denver, CO. A coupled energy and economic analysis demonstrates the critical role played by the grid in the economic feasibility of achieving net-zero energy, as well as the mutual benefit of on-site energy storage. A VOS case study is performed for Sioux Center Municipal Utilities in northwest Iowa leveraging five years of municipal power consumption coupled with real PV electricity generation data. A dual optimization approach develops an electric rate structure that best aligns with and incentivizes development toward optimal VOS design. Together, these studies affirm that while local technical solutions and optimal designs may differ, the principles of sustainable design can be applied and followed consistently such that RES can grow and flourish in communities across the globe.
Keywords: load duration curve; net-zero energy district; value of solar; load/generation balance; levelized cost of energy; photovoltaic optimization